EFFECT OF TEMPERATURE AND HUMIDITY ON EPISTAXIS IN HAZARA DIVISION - Muhammad, Raza; Khan, Farida; Abrar, Said ul; Khan, Muhammad Riaz; Rehman, Fazal; Iqbal, Johar; Khan, Munib (Journal of Ayub Medical College Abbottabad, 2013)
Background: Epistaxis is one of the commonest ENT emergencies and is experienced by up to 60% of people in their lifetime, with 6% requiring medical attention. The objective of the study was to determine the frequency of primary epistaxis and its relationship with temperature and relative humidity. Methods: This cross sectional study included 460 patients with epistaxis attending the ENT Department of Ayub Medical College, Abbottabad. Daily temperature and humidity record was obtained from the department of Hydrology and Meteorology of Hazara Division. The results of four hundred and sixty patients were analyzed for the effect of temperature and humidity on the frequency of epistaxis. Data was analysed using SPSS-11. Pearson's r was calculated to determine correlation between different variables. Results: A total of 460 patients were included, out of which 206 (44.8%) had primary epistaxis. The frequency of primary epistaxis was seen to be higher during the cold period from October to March. Statistical analysis showed good negative correlation between temperature and primary epistaxis (r=-0.948) while average correlation with humidity (r=-0.445). Conclusion: The relationship between temperature and primary epistaxis was good while that with relative humidity was average. Keywords: Temperature, Epistaxis, Relative humidity.